FRI0006 Class 3 Semaphorins Modulate The Invasive Capacity of Rheumatoid Arthritis Fibroblast-like Synoviocytes. (15th July 2016) - García Pérez, S.; Malvar Fernandez, B.; Tang, M.W.; Newsom, S.P.; Radstake, T.R.; Baeten, D.L.; Tak, P.P.; Reedquist, K.A.
Abstract : Background: The semaphorin family is a large group of proteins initially described in axon guidance. However, semaphorins also play a role in other processes such as the regulation of immunity, angiogenesis, apoptosis and cell migration and invasion. Moreover, semaphorins have been related with the pathogenesis of multiple sclerosis, myocarditis, atherosclerosis and cancer. However, the potential role of class 3 semaphorins in rheumatoid arthritis (RA) remains unknown. Objectives: The aim of this study was to analyze the role of class 3 semaphorins in the pathology of RA. Methods: mRNA expression of class 3 semaphorins in the synovial tissue of early, DMARD-naive arthritis patients was analyzed by (q)uantitative PCR. RA FLS were stimulated for 4h with IL-1β, TNF or LPS. and mRNA and expression of class 3 semaphorins was analyzed by qPCR. RA FLS were stimulated with Sema3A, Sema3B or Sema3F in the presence or absence of PDGF. Cell migration and invasion were determined using wound closure motility and transwell invasion assays, respectively. Matrix metalloproteinase mRNA and protein expression was determined by qPCR array and luminex. PlexinA1 and neuropilin-1 expression were knocked-down by siRNA-mediated silencing. ERK and Rac1 activation were determined by immunoblot. Results: mRNA expression of class 3 semaphorins in the synovial tissue of early arthritis patients negatively and significantly correlated with the mRNA expression of inflammatory mediators and the disease activity parameters of these patients. Moreover, Sema3B, Sema3C, Sema3F and Sema3G mRNA expression were significantly lower in early arthritis patients who developed persistent disease compared with patients with self-limiting disease after 2 years follow-up. Sema3F and Sema3B expression were significantly lower in patients that developed RA after 2 years of follow-up compared to those who remained as undifferentiated arthritis patients. FLS expression of Sema3A was significantly induced after IL-1, TNF or LPS stimulation, while the expression of Sema3B and Sema3F was down-regulated. Functional assays showed that Sema3A significantly induced the migration and invasion of FLS. In contrast, Sema3B and Sema3F reduced spontaneous FLS migration and PDGF-induced cell invasion. These effects were associated withthe differential regulation of MMP-1, MMP-3 and MMP-8 by these semaphorins, and were mediated by the receptor PlexinA1 and the co-receptor NRP-1. Finally, we observed that class 3 semaphorins reduced the PDGF-induced ERK and Rac1 activation. Conclusions: Our data demonstrate that class 3 semaphorins are differentially expressed in the synovium of early patients depending on the severity and the progression of the disease and that Sema3A, Sema3B and Sema3F play an important role in the invasive capacity of RA FLS. Together, class 3 semaphorins and their receptors could be useful biomarkers and promising therapeutic targets for the treatment of RA. Disclosure of Interest: None declared